Analysis of Students' Ability in Solving Physics Problems on the Concept of Thermodynamics for Class XI SMAN 2 Binongko - Halmuniati, Halmuniati; Kurniawan, Kurniawan; Zainuddin, Zainuddin; Asmin, La Ode; Isa, La; Burhan, Burhan (Universitas Islam Negeri Ar-Raniry, 2025)
The majority of physics learning in high school is still considered difficult to understand and has an impact on low ability to solve the problems given. This research aims to (1) determine students' knowledge abilities in solving physics problems on thermodynamic concepts. (2) Knowing students' understanding abilities in solving physics problems on thermodynamic concepts. (3) Knowing students' application abilities in solving physics problems on thermodynamic concepts. (4) a description of students' analytical abilities in solving physics problems on thermodynamic concepts. This research method uses a quantitative descriptive research design. The subjects in this research were class XI students at SMAN 2 Binongko. The data collection technique used essay test questions which were then given to class XI students. The research results show that (1) Students' ability to solve physics questions at the knowledge level (C1) is categorized as high with a percentage of 44%. (2) Students' ability to solve physics questions at the understanding level (C2) is categorized as moderate with a percentage of 36%. (3) Students' ability to solve physics questions at the applied level (C3) is categorized as very low with a percentage of 64%. (4) Students' ability to solve physics questions at the analysis level (C4) is categorized as very low with a percentage of 75%.